2019
DOI: 10.1037/xge0000498
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge is power: Prior knowledge aids memory for both congruent and incongruent events, but in different ways.

Abstract: Events that conform to our expectations, that is, are congruent with our world knowledge or schemas, are better remembered than unrelated events. Yet events that conflict with schemas can also be remembered better. We examined this apparent paradox in 4 experiments, in which schemas were established by training ordinal relationships between randomly paired objects, whereas event memory was tested for the number of objects on each trial. Better memory was found for both congruent and incongruent trials, relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
107
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(149 citation statements)
references
References 111 publications
15
107
3
Order By: Relevance
“…Here, larger PEs were associated with a relative decrease in responding with locations that were consistent with the old schema, apparent in reduced evidence of responses -90 degrees from the current schema (i.e., at the position of the old schema for the inconsistent conditions) compared to what was observed in the consistent conditions. My work reveals that similar neural mechanisms underlie PE-based updating of long-term memory schemas, and short-term beliefs (Bennett et al, 2015;Jepma et al, 2018Jepma et al, , 2016Kolossa et al, 2015), consistent with what has been proposed in the literature (van Kesteren et al, 2012), and what has been shown for other types of memory (Greve et al, 2017(Greve et al, , 2019Pine et al, 2018;Sinclair & Barense, 2018.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Here, larger PEs were associated with a relative decrease in responding with locations that were consistent with the old schema, apparent in reduced evidence of responses -90 degrees from the current schema (i.e., at the position of the old schema for the inconsistent conditions) compared to what was observed in the consistent conditions. My work reveals that similar neural mechanisms underlie PE-based updating of long-term memory schemas, and short-term beliefs (Bennett et al, 2015;Jepma et al, 2018Jepma et al, , 2016Kolossa et al, 2015), consistent with what has been proposed in the literature (van Kesteren et al, 2012), and what has been shown for other types of memory (Greve et al, 2017(Greve et al, , 2019Pine et al, 2018;Sinclair & Barense, 2018.…”
Section: Discussionsupporting
confidence: 85%
“…Previous research has speculated that updating of knowledge structures such as schemas might rely on a mismatch between a prediction and the encountered information (Richter et al, 2019;van Kesteren et al, 2012), and similar processes have been observed in other memory systems (Greve et al, 2019;Henson & Gagnepain, 2010;Krawczyk, Fernández, Pedreira, & Boccia, 2017;Pine et al, 2018). However, due to the absence of sufficiently sensitive methods to measure trial-by-trial differences in schema updating in the laboratory prior to the development of continuous report memory tasks, it has only recently been possible to visualise adjustments to pre-existing schemas in the aftermath of encountering schemainconsistent information (Richter et al, 2019).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…van Kesteren et al, 2012), in which information that can be associated with prior knowledge (the memory schema) is more likely to be consolidated, updating this schema (Tse et al, 2007). Such prior knowledge effects can facilitate understanding of movies and stories (M. T. R. van Kesteren, Fernandez, Norris, & Hermans, 2010), face recognition (Liu, Grady, & Moscovitch, 2018) and associative representations (Greve et al, 2019;Ozubko, Moscovitch, & Winocur, 2017). Using a series of stimulus presentations, these studies show that prior knowledge, acquired during a training phase, affects performance in the following perceptual task.…”
Section: Introductionmentioning
confidence: 87%